Carvacrol inhibits Streptococcus pyogenes biofilms by suppressing the expression of genes associated with quorum-sensing and reducing cell surface hydrophobicity. (August 2022) - Wijesundara, Niluni M.; Lee, Song F.; Rupasinghe, H.P. Vasantha
Abstract: Streptococcus pyogenes is a leading cause of chronic and acute infections, including streptococcus pharyngitis. Biofilm formation by S. pyogenes can cause tolerance against antibiotics. Although penicillin remains the first choice of antibiotic for S. pyogenes, alternative approaches have gained interest due to treatment failures and hypersensitive individuals. Carvacrol is a monoterpenoid from herbal plants with selective biocidal activity on S. pyogenes . Therefore, the present study reveals the efficacy of carvacrol in inhibiting and eradicating S. pyogenes biofilm . The antibiofilm activities were investigated using colorimetric assays, microscopy, cell surface hydrophobicity, gene expression analysis, and in-silico analysis. Carvacrol also showed a minimum biofilm inhibitory concentration (MBIC) against S. pyogenes of 125 μg/mL. The electron microscopic and confocal microscopic analyses revealed a dose-dependent suppression of biofilm formation and a reduction in the biofilm thickness by carvacrol. Carvacrol also inhibited the biofilm-associated virulence factors such as cell surface hydrophobicity. Quantitative real-time polymerase chain reaction analysis showed the downregulation of speB, srtB, luxS, covS, dltA, ciaH, and hasA genes involved in biofilm formation. The results suggested the therapeutic potential of carvacrol against biofilm-associated streptococcal infections. Graphical abstract: Image 1 Highlights: Carvacrol inhibits the formation of Streptococcus pyogenes biofilm in a dose-dependent manner. Carvacrol eradicates the pre-formed mature biofilms. Genes of speB, srtB, luxS, covS, dltA, ciaH, and hasA downregulated by carvacrol. Carvacrol exhibits potential against biofilm-associated streptococcal infections.